2021
DOI: 10.1093/jrr/rraa134
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical activity/exercise habits and the frequency of new onset of lifestyle-related diseases after the Great East Japan Earthquake among residents in Fukushima: the Fukushima Health Management Survey

Abstract: The effect of exercise habits on the increased incidence of lifestyle-related diseases among residents of the evacuation area in Fukushima Prefecture after the Great East Japan Earthquake is not well characterized. This study examined the influence of exercise habits on the frequency of new onset of lifestyle-related diseases in the aftermath of the earthquake using data from the Fukushima Health Management Survey (FHMS). Of the 32 289 individuals (14 004 men and 18 285 women) aged 40–90 years who underwent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“… 29 In addition, an active lifestyle was found to reduce the risk of developing dyslipidemia 3–4 years after the disaster. 32 Furthermore, regarding associations between dietary patterns and the risk of lifestyle-related diseases, a Japanese vegetable diet pattern could reduce the risk of developing dyslipidemia and CKD. 33 , 34 …”
Section: Methods and Resultsmentioning
confidence: 99%
“… 29 In addition, an active lifestyle was found to reduce the risk of developing dyslipidemia 3–4 years after the disaster. 32 Furthermore, regarding associations between dietary patterns and the risk of lifestyle-related diseases, a Japanese vegetable diet pattern could reduce the risk of developing dyslipidemia and CKD. 33 , 34 …”
Section: Methods and Resultsmentioning
confidence: 99%
“…In our study, 24% of the elderly group and 30% of all residents were undecided regarding their intention to return, and 72.6% of those who wanted to return to Okuma reported poor physical component scores (p = 0.035). Evidence regarding the long-term physical health effects of evacuation has already been established, explained perhaps by the increased stress and the lack of resources available at evacuation sites to maintain a healthy lifestyle [ 58 ], both of which are exacerbated in the elderly. Similar results were demonstrated by Borglin et al in a non-disaster setting in Sweden, where reduced physical mobility was associated with lower self-reported quality of life, and this was more pronounced in elderly women [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been several reports of a significant increase in the prevalence of dyslipidemia among residents of the evacuation area after the NPP accident, there have been no comparisons between the evacuation area and other areas [13,24,25]. In this study, we examined the prevalence of dyslipidemia before and after the disaster throughout Fukushima Prefecture, including areas outside of the evacuation area, using the NDB and found that although a gradual increase in the prevalence of dyslipidemia was observed after the disaster throughout Fukushima Prefecture, a rapid increase in the prevalence was observed from FY2011 to FY2013 in the evacuation area, and the prevalence has continued to be significantly higher than in areas not affected by the disaster.…”
Section: Discussionmentioning
confidence: 99%